2009
DOI: 10.5551/jat.no224
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Oxidized Lipoprotein(a) Concentration with Coronary Artery Disease: Potential Role of Oxidized Lipoprotein(a) in the Vasucular Wall

Abstract: Aim:A new antibody reacted with an epitope in Lp(a) that has undergone oxidation treatment, but is not present in native Lp(a), was developed. Thus, we determined serum oxidized Lp(a) concentration in healthy volunteers, and coronary artery disease (CAD), diabetes mellitus (DM), and hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Using this antibody, they developed a ELISA to measure Lp(a) modified by oxidative stress, and found that hypertensive patients with complications showed a significantly higher level of oxidized Lp(a) in serum than did normotensive subjects, whereas there was no significant difference in native Lp(a) between normotensive and hypertensive subjects. Morishita R et al [38] reported that ox-Lp(a) level in CAD patients with diabetes mellitus was significantly higher than in healthy volunteers. Moreover, serum ox-Lp(a) concentration showed a significant positive correlation with pulse wave velocity, an index of arteriosclerosis .…”
Section: Oxidized Lp(a) Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Using this antibody, they developed a ELISA to measure Lp(a) modified by oxidative stress, and found that hypertensive patients with complications showed a significantly higher level of oxidized Lp(a) in serum than did normotensive subjects, whereas there was no significant difference in native Lp(a) between normotensive and hypertensive subjects. Morishita R et al [38] reported that ox-Lp(a) level in CAD patients with diabetes mellitus was significantly higher than in healthy volunteers. Moreover, serum ox-Lp(a) concentration showed a significant positive correlation with pulse wave velocity, an index of arteriosclerosis .…”
Section: Oxidized Lp(a) Assaymentioning
confidence: 99%
“…The degree of oxidized apo(a) or apoB protein of Lp(a) has been detected to estimate circulating ox-Lp(a) levels [37][38][39][40]. Yamada et al [37] obtained a new 161E2 monoclonal antibody to react with oxidized Lp(a) but not with native Lp(a).…”
Section: Oxidized Lp(a) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact elevated Lp(a) level is believed to promote atherosclerosis via Lp(a)-derived cholesterol entrapment in the intima, inflammatory cell recruitment and/or via the binding of pro-inflammatory-oxidised LDL (17)(18)(19)(20)(21)(22). Elevated Lp(a) level promote also thrombosis via the inhibition of fibrinolysis with enhancement of clot stabilization as well as via enhancement coagulation via the inhibition of tissue factor pathway inhibitor.…”
Section: Editorialmentioning
confidence: 99%
“…Ox-Lp(a) levels have been reported to be present in newborns and children 11) , and increased in rheumatoid arthritis patients with excessive cardiovascular events 12) . Furthermore, elevated ox-Lp(a) levels have been found to be associated with the presence of stable coronary artery disease (CAD) and acute coronary syndromes (ACS), and with the severity of ACS [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%